Critical Thinking Skills in Solving Mathematical Problems Based on Thinking and Feeling Personality Types of Grade 8 Students - Ilhamuddin; Irwan Akib; Sukmawati; Hildayanti (International Journal of Learning Reformation in Elementary Education, 2026)
Critical thinking skills are essential competencies in mathematics learning, but learning practices often emphasize final results rather than students' thinking processes. These differences in thinking processes are inseparable from personality characteristics, particularly the Thinking and Feeling types. This study aims to describe and compare students' critical thinking skills in solving mathematical problems based on the Thinking and Feeling personality types. This study uses a descriptive qualitative approach with two subjects, eighth-grade students at Unismuh Makassar Junior High School, each representing the Thinking and Feeling personality types. Data were obtained through the MBTI personality test, critical thinking ability tests in the form of essay questions, semi-structured interviews, and documentation, then analyzed using the Miles, Huberman, and Saldaña model with time triangulation to ensure data validity. The results showed that both personality types were able to fulfill the six indicators of critical thinking, namely interpretation, analysis, inference, evaluation, explanation, and self-regulation, but through different thinking processes. Students with the Thinking type showed a more logical, systematic, and efficient thinking pattern from the early stages, while students with the Feeling type displayed a more gradual, contextual, and reflective thinking process. These findings confirm that critical thinking in mathematics is multidimensional and influenced by personality. This study contributes to enriching the study of mathematical critical thinking and provides practical implications for teachers to design adaptive learning according to students' thinking characteristics.